Europe's perennial 'outsiders': A processual approach to Roma stigmatization and ghettoization. (September 2017) - Powell, Ryan; Lever, John
This article draws on the theoretical work of Norbert Elias and Loïc Wacquant in seeking to understand the stigmatized and marginalized position of the Roma population within Europe. The article argues that the persistent persecution of Roma, reflected in social policy, cannot be understood without reference to long-term social processes which shape the nature of the asymmetric power relations between Roma and non-Roma. Elias's theory of established–outsider relations is applied at the intra-state European level in arguing that Roma constitute a cross-border 'outsider' group; with their intense stigmatization explained and perpetuated by a common set of collective fantasies which are maintained through complex group processes of disidentification, and which result in Roma being seen as of lesser human worth. Wacquant's theoretical concept of the 'ghetto' is then drawn upon to show how the manifestations of stigmatization for the stigmatized are at once psychological, social and spatial . The article suggests that the synthesis of the two theorists' concepts allows for an approach that can expose the way in which power is exercised within and through group relations. Such an approach emphasizes the centrality of the interdependence between Roma and non-Roma, and the fluctuating power balance that characterizes that relationship across time and space. The article concludes that, while existing research focused on policy and outcomes is useful in understanding the negative contemporary experiences of Roma populations, they need to be understood in the context of wider social processes and historical continuities in seeking to elucidate how these processes shape policies and contribute to social and spatial marginalization.